Documental radiofónico sobre la oralidad como subproducto literario segregado por la literatura escrita - Montalván Briones, Ramón Rolando (2016)
Orality has been regarded by many cultures as a tissue fabric, weaving relations environment itself; that oral enunciation involves a ritual to myth, the story that has existed at all times in all people, what proffers a universal category because this is perhaps the most expressive power of popular culture. Writing, on the other hand, represents the gentrification of the spoken word that personifies a tiny proportion of cultures, reflecting that when from the West the concept of literature written on the orality as a requirement of civilizing category of language was erected (as it has happened with traditional medicine, social sciences, technology, etc.), ethnocentrism allowed the domain also ways of communicating, leaving aside the construction of the story from the spoken with all the symbolic baggage word that feeds the social and cultural memory of peoples. Thus the duality of knowledge also in the literary was generated and linked to orality with prehistory and writing history. This research work aims to identify the cultic, economic, historical, social and political patterns erected to writing about orality, in order to strengthen communication processes and literary dissemination in favor of cultures of primary oral tradition, from the recreation of his communicational and literary discourse through myths, musicality, languages and socio-cultural context in a radio documentary